Between film and photography: the bubble of blood in The Family of Disorder. (11th March 2019) - Elduque, Albert
Abstract: Founded within the context of the Brazilian military dictatorship, the film company Belair was one of the most radical attempts to cultivate a cinema in the spirit of Tropicalism: its works are distinguished by parodies of genre filmmaking, a carnivalesque celebration of the body, and a profound investment in subversive politics. Led by filmmakers Rogério Sganzerla and Júlio Bressane and actress Helena Ignez, Belair produced six films between January and March 1970, when the team was forced into exile. A Família do Barulho / The Family of Disorder, directed by Bressane, contains one of the most striking sequences in all of Belair's productions. Its portrait of a nuclear family in constant tension ends up with the three main characters looking straight into the camera and suffering in front of an unknown, invisible danger: a young man has a wound on his face; another covers his face with his hands in a liminal state; and a woman, played by Ignez, vomits a bloody slobber. Following Brigitte Peucker's exploration of the relationship between cinema's impurity, stillness and the cinematic body, as well as Raymond Bellour's analysis of some dispositifs that anticipated the movement of cinema from the immobility of death, I argue that these images exist in a territory between different media, and between life and death: they are intersections of the liberating dynamism of cinema and the enforced stillness of photography, which evokes police mugshots, the menace of firing squads, and the ghostly quality of wax figures. I focus particularly on the case of Ignez and her bloody mouth, which chime with the tropicalist exploration of the grotesque and the intermedial quality of the cinematic body.